A randomised controlled trial for overweight and obese parents to prevent childhood obesity - Early STOPP (STockholm Obesity Prevention Program) - Cao Yingting; Johansson Elin; Karlsson Håkan; Ekstedt Mirjam; Ek Anna; Svensson Viktoria; Sobko Tanja; Hagströmer Maria; Marcus Claude (BMC, 2011)
Abstract Background Overweight and obesity have a dramatic negative impact on children's health not only during the childhood but also throughout the adult life. Preventing the development of obesity in children is therefore a world-wide health priority. There is an obvious urge for sustainable and evidenced-based interventions that are suitable for families with young children, especially for families with overweight or obese parents. We have developed a prevention program, Early STOPP, combating multiple obesity-promoting behaviors such unbalanced diet, physical inactivity and disturbed sleeping patterns. We also aim to evaluate the effectiveness of the early childhood obesity prevention in a well-characterized population of overweight or obese parents. This protocol outlines methods for the recruitment phase of the study. Design and methods This randomized controlled trial (RCT) targets overweight and/or obese parents with infants, recruited from the Child Health Care Centers (CHCC) within the Stockholm area. The intervention starts when infants are one year of age and continues until they are six and is regularly delivered by a trained coach (dietitian, physiotherapist or a nurse). The key aspects of Early STOPP family intervention are based on Swedish recommendations for CHCC, which include advices on healthy food choices and eating patterns, increasing physical activity/reducing sedentary behavior and regulating sleeping patterns. Discussion The Early STOPP trial design addresses weaknesses of previous research by recruiting from a well-characterized population, defining a feasible, theory-based intervention and assessing multiple measurements to validate and interpret the program effectiveness. The early years hold promise as a time in which obesity prevention may be most effective. To our knowledge, this longitudinal RCT is the first attempt to demonstrate whether an early, long-term, targeted health promotion program focusing on healthy eating, physical activity/reduced sedentary behaviors and normalizing sleeping patterns could be effective. If proven so, Early STOPP may protect children from the development of overweight and obesity. Trial registration The protocol for this study is registered with the clinical trials registry clinicaltrials.gov, ID: ES-2010)